Evidence of hafting traces on lithics end-scrapers at maripe cave site (Santa Cruz, Argentina) - Lynch, Virginia (2015)
This paper presents a review related to using microwear analysis to identify hafting process in archaeological contexts and also presents actualistic and archaeological information of hafting traces. In this way, the case of mid-Holocene (yj00-3000 BP ca. years) end-scrapers from Maripe Cave site (Santa Cruz Province, Argentina) provides abundant evidence to identify this kind of traces that are often difficult to recognize. In this research, we also study the relationship between use mode and tool shapes that can be used to interpret how hafted tools were used in the past.